2014
DOI: 10.1021/ie402633n
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Toluene by a Selective Ferrous Ion Activated Persulfate Oxidation Process

Abstract: The Fe 2+ -activated persulfate (PS) oxidation of toluene was evaluated using single-factor tests and response surface methodology (RSM). The results indicated the degradation efficiency increased as the PS and Fe 2+ concentrations increased, while excessive dosages inhibited the degradation efficiency. The pH had an insignificant effect on the degradation of toluene. Based on the RSM optimization approach, the degradation efficiency reached a maximum of 84.4%. The main intermediates were also separated and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 122 publications
(33 citation statements)
references
References 47 publications
5
28
0
Order By: Relevance
“…Furthermore, the coefficient of variation (CV) describes the extent to which the data were dispersed, with lower values giving better reproducibility (Ahmad et al 2005;Sekaran et al 2014). The present CV value (CV=9.55 %) indicated that the variation in the mean value was satisfactory, being within the acceptable range of 0.5-13.5 % (Long et al 2013(Long et al , 2014aSekaran et al 2014). Finally, adequate precision is used to measure the signal-to-noise ratio.…”
Section: Response Surface Evaluationmentioning
confidence: 61%
See 4 more Smart Citations
“…Furthermore, the coefficient of variation (CV) describes the extent to which the data were dispersed, with lower values giving better reproducibility (Ahmad et al 2005;Sekaran et al 2014). The present CV value (CV=9.55 %) indicated that the variation in the mean value was satisfactory, being within the acceptable range of 0.5-13.5 % (Long et al 2013(Long et al , 2014aSekaran et al 2014). Finally, adequate precision is used to measure the signal-to-noise ratio.…”
Section: Response Surface Evaluationmentioning
confidence: 61%
“…Thus, in the flushing effluents, SO 4 : − may oxidize toluene at a faster rate than it oxidizes straight-chain aliphatic hydrocarbon surfactants. Indeed, selective oxidation of toluene in SDS flushing effluents was observed in our previous studies (Long et al 2013(Long et al , 2014a. Therefore, the objective of the present study was to optimize toluene removal for SDS recovery in flushing effluents from the electro/Fe 2+ /persulfate process using single-factor tests and response surface methodology (RSM).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations